2015
DOI: 10.1179/1362171815y.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma electrolytic oxidation coating on joining metal to plastic

Abstract: Joining of magnesium alloy to polyethylene without adhesive using a newly developed friction lap welding technology was investigated. The polyethylene and magnesium alloy were hard to be joined together without surface premodification due to the lack of polar groups on polyethylene surfaces. Strong hybrid joints were achieved after the polyethylene was treated by corona discharge, and the magnesium alloy was subjected to plasma electrolytic oxidation treatment. Scanning electron microscope and high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…20,21) MgO for Mg alloy/plastic, and MgO and Al 2 O 3 for Al alloy/ plastic were observed as oxide layers of these metals at these interfaces. It was indicated that these materials were also joined because of the Coulomb's force (hydrogen bonding) between the oxide layers of the metals and the polar group of plastics as well as plain carbon steel/plastic, as shown in Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…20,21) MgO for Mg alloy/plastic, and MgO and Al 2 O 3 for Al alloy/ plastic were observed as oxide layers of these metals at these interfaces. It was indicated that these materials were also joined because of the Coulomb's force (hydrogen bonding) between the oxide layers of the metals and the polar group of plastics as well as plain carbon steel/plastic, as shown in Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, researchers have investigated techniques for fusion bonding of dissimilar materials using various heat sources, such as laser joining, [7][8][9] ultrasonic welding, 10) induction heating, 11) friction spot joining, 12,13) friction stir welding, 14,15) and friction lap joining (FLJ). [16][17][18][19][20][21][22][23][24] FLJ, which is a novel direct joining method, is derived from a FSW process. The tool used in FSW consists of a stirring probe, to facilitate material flow, and a shoulder part; however, the tool used in FLJ does not require such a probe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, PEO coating has been used as an intermediary for joining metal to polymer using friction lap welding. [15] PEO treatment has been used to form oxide coatings on valve metals such as aluminum, magnesium, titanium, and their alloys. [16] The PEO treatment is an oxidizing process in an aqueous electrolyte through a series of electrolytic plasma discharges.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the physical and chemical dissimilarities of individual materials, the development of suitable joining technologies is essential for enabling multi-material auto bodies. Recently, extensive research has been conducted for joining carbon fiber composites to various metals (e.g., aluminum or magnesium alloys), using laser welding [7,8], friction stir blind riveting [9], friction spot joining [10][11][12], ultrasonic welding [13], adhesive bonding [14], friction lap welding [15,16], friction-based injection clinching joining [17], self-piercing riveting [18,19], and hybrid bonding (adhesive + mechanical fastening) [20][21][22]. In addition, very limited work has been focused on joining carbon fiber composites to steel [8,14,23,24].…”
Section: Introductionmentioning
confidence: 99%